2007
DOI: 10.1111/j.1365-2141.2007.06732.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation: a comparison of assays using platelet‐poor and ‐rich plasma and whole blood samples from healthy controls and patients with a history of venous thromboembolism

Abstract: Summary We have developed a whole blood thrombin generation (TG) assay whereby TG is initiated with a low‐tissue factor concentration and monitored using a fluorogenic thrombin substrate. Significantly higher values were found in blood samples from 50 patients with a history of venous thromboembolism (VTE) compared with 31 healthy controls (HC), for peak height (P = 0·0034) and endogenous thrombin potential (ETP) (P = 0·0027). Results from 31 VTE patients and the 31 controls in the absence of corn trypsin inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 19 publications
3
49
0
1
Order By: Relevance
“…ETP and peak thrombin were found to be increased in patients with a history of VTE compared to healthy individuals and were related to the risk of a first event of VTE. 56,57 Hron et al reported on the relationship between recurrent VTE and peak thrombin generation and concluded that patients with a peak thrombin less than 300 nM (lower tertile) had a significantly lower risk of recurrence compared to patients with peak thrombin generation above the upper tertile of 400 nmol/L (relative risk [95% CI]: 0.37 [0.20 to 0.67]). 58 Data on the ETP and other parameters of the TG assay are not given in this report.…”
Section: Thrombin Generationmentioning
confidence: 99%
“…ETP and peak thrombin were found to be increased in patients with a history of VTE compared to healthy individuals and were related to the risk of a first event of VTE. 56,57 Hron et al reported on the relationship between recurrent VTE and peak thrombin generation and concluded that patients with a peak thrombin less than 300 nM (lower tertile) had a significantly lower risk of recurrence compared to patients with peak thrombin generation above the upper tertile of 400 nmol/L (relative risk [95% CI]: 0.37 [0.20 to 0.67]). 58 Data on the ETP and other parameters of the TG assay are not given in this report.…”
Section: Thrombin Generationmentioning
confidence: 99%
“…The method is, however, not applicable for measuring TG in whole blood. Variable quenching of the fluorescent signal by hemoglobin and red blood cells that sediment, cluster, and retract with the clot lead to highly erratic signals (10,11 ). The use of fibrin as an indicator product for TG in whole blood, as in thromboelastography (TEG), does not reflect the thrombin-generating capacity of patients, because fibrinogen as a substrate is quickly exhausted and therefore informs about TG only at the earliest phases of the coagulation process (5,12 ).…”
Section: © 2012 American Association For Clinical Chemistrymentioning
confidence: 99%
“…Ayrıca literatürde tromboz riski ile ilgili yapılmış çalışmalarda, trombin formasyonundaki çeşitliliklere bağlı olarak TGA testi parametrelerinin hepsi artmaktadır; fakat en önemli ve trombin oluşumunu gösteren en hassas parametre ETP değeridir. [39][40][41][42] Macey ve ark.nın preeklamptik gebeler, sağ-lıklı gebeler ve sağlıklı gebe olmayan kadınlarda yaptığı çalışmada ise duraklama zamanı ve pik zamanı preeklamptik gebelerde preeklampsisi olmayan gebelere göre, preeklampsisi olamayan gebelerde ise sağlıklı kadınlara göre daha kısa bulunmuştur. 35 Bu çalışmada hastaların trombofili göstergeleri hakkında veri bulunmamaktadır.…”
Section: Discussionunclassified